Cooking oil sales boost incomes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In several countries in Africa, small-scale entrepreneurs are boosting their incomes by producing cooking oil. Utilizing an innovative seed press called the ram press, some village women in Tanzania have been able to earn more than a typical...